2014
DOI: 10.1186/s12865-014-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomy in FcγRIIB deficiency and autoimmune-prone SLAM haplotype clarifies the roles of the Fc receptor in development of autoantibodies and glomerulonephritis

Abstract: BackgroundThe significance of a unique inhibitory Fc receptor for IgG, FcγRIIB (RIIB), in the prevention of spontaneous production of autoantibodies remains controversial, due mainly to the fact that the RIIB locus is adjacent to the autoimmune-related SLAM locus harboring the genes coding for signaling lymphocyte activation molecules, making it difficult to isolate the effect of RIIB deletion from that of SLAM in gene-targeted mice. Our objective was to determine the influence of RIIB deletion on the spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
(56 reference statements)
4
11
0
Order By: Relevance
“…Consistent with previous reports [18, 19], and the recent report by Kanari et al, [57], we also observe that B6.129.RIIBKO mice develop pathogenic autoAbs and lupus nephritis. In line with the effects of 129-SLAMs and FcγRIIB deficiency on Spt-GC responses, we observe an independent effect of each of them on the accumulation of class-switched autoAbs, further suggesting the generation of autoreactive B cells through the GCs (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous reports [18, 19], and the recent report by Kanari et al, [57], we also observe that B6.129.RIIBKO mice develop pathogenic autoAbs and lupus nephritis. In line with the effects of 129-SLAMs and FcγRIIB deficiency on Spt-GC responses, we observe an independent effect of each of them on the accumulation of class-switched autoAbs, further suggesting the generation of autoreactive B cells through the GCs (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…They have not, however, examined either induced or spontaneous GC B cell and Tfh responses in these mice. Consistent with our observations, a recent study by Takai and co-workers reported enhanced Spt-GC B cell formation in the presence of 129-SLAM genes alone [57]. However, this study did not examine the effect of 129-SLAMs on Tfh formation and functions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Initially, FccRIIB -/mice were reported to develop lupus-like disease [32]. Later, development of the disease turned out to require the 129 mouse strain-derived autoimmune-prone SLAM haplotype, which is closely located to the FccRIIB locus on the chromatin, and FccRIIB -/mice on the C57BL/6 background do not develop autoimmune disease [33]. Thus, SHIP1 appears to be activated by a mechanism independent of inhibitory receptors to regulate autoimmune disease.…”
Section: Inhibitory B Cell Co-receptors and Slementioning
confidence: 99%
“…The addition of Yaa locus to B6.FcgRIIb 2/2 mice results in the development of lupus nephritis with 30% penetrance at the age of 10-12 mo (13). Thus, the deletion of FcgRIIb, the presence of SLAM haplotype 2, and the Yaa locus all contribute to the development of severe autoimmunity (14,15).…”
mentioning
confidence: 99%